Pengaruh Penggunaan Abu Cangkang Sawit Dari Boiler Terhadap Sifat Fisik Eternit - Haspiadi Haspiadi; Eko Heryadi (Jurnal Riset Teknologi Industri, 2016)
Shell burning oil as a fuel in the boiler produces ash by 15% which contains silica (SiO2) is quite high at 68.82% and alumina (Al2O3) of 3.08%. Silica and alumina are required compounds in the mixture making various kinds of buildings materials one of which is plasterboard. The purpose of this study is to asesess the potential of oil shell ash a raw material in the manufacture of plasterboard formed to analyze the physical properties. Ash from palm oil shell is along with bonding cement, lime and fiber. The component of plasterboard is 20%, 40%, 60% and 80%, also 0% as a control. The plasterboard making was done by using some simple equipment. The best result of analysis according to examination method for fiber cements sheets in SNI 15 0233-1989 is obtained the maximum composition is 60% ash, 20% lime, 15% cement and 5% fiber. At this composition has a good shape, good nail strength,  white natural color, the density of water is not happening dropping water and low the water absorption = 29,3% and also low weight of content = 7,7 g/cm3.